2023
DOI: 10.1093/mnras/stad1002
|View full text |Cite
|
Sign up to set email alerts
|

Metal line emission from galaxy haloes at z ≈ 1

Abstract: We present a study of the metal-enriched halo gas, traced using Mg ii and [O ii] emission lines, in two large, blind galaxy surveys – the MUSE (Multi Unit Spectroscopic Explorer) Analysis of Gas around Galaxies (MAGG) and the MUSE Ultra Deep Field (MUDF). By stacking a sample of ≈600 galaxies (stellar masses $\rm M_*$ ≈106 − 12 $\rm M_\odot$), we characterize for the first time the average metal line emission from a general population of galaxy haloes at 0.7 ≤ z ≤ 1.5. The Mg ii and [O ii] line emission extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 175 publications
0
6
0
Order By: Relevance
“…Similarly, VSF measurements have also been reported for QSO host halos on scales from 10 kpc to ≈60 kpc based on lineemitting nebulae discovered around luminous QSOs (Chen et al 2023). However, detections of line-emitting nebulae around typical galaxies or galaxy groups remain extremely rare beyond the nearby Universe (e.g., Chen et al 2019;Dutta et al 2023) and even for extreme systems like QSO nebulae and intracluster medium the ground-based seeing imposes a limit on the smallest scale one can probe with IFS observations. Extending VSF studies to the CGM around galaxies representative of the field population on scales below 1 kpc requires a different approach.…”
Section: Methodsmentioning
confidence: 69%
“…Similarly, VSF measurements have also been reported for QSO host halos on scales from 10 kpc to ≈60 kpc based on lineemitting nebulae discovered around luminous QSOs (Chen et al 2023). However, detections of line-emitting nebulae around typical galaxies or galaxy groups remain extremely rare beyond the nearby Universe (e.g., Chen et al 2019;Dutta et al 2023) and even for extreme systems like QSO nebulae and intracluster medium the ground-based seeing imposes a limit on the smallest scale one can probe with IFS observations. Extending VSF studies to the CGM around galaxies representative of the field population on scales below 1 kpc requires a different approach.…”
Section: Methodsmentioning
confidence: 69%
“…We present the differences between the measured metallicities for individual sources and the values predicted by the MZR using our best-fit value of γ for each galaxy in order to control for SFR in Figure 11, with the points color coded based on whether the galaxies reside in isolated (black) or group (gold) environments. We used our group catalog developed in Dutta et al (2023) to separate galaxies by environment, where the catalog was obtained by running a friends-of-friends algorithm on the galaxy sample with reliable redshifts using linking lengths of 400 kpc in the transverse spatial direction and 400 km s −1 in the line-of-sight velocity direction.…”
Section: The Role Of Environmentmentioning
confidence: 99%
“…However, the diffuse nature and cool-warm temperature range (T ≈ 10 4 -10 6 K) of the IGM/CGM around typical galaxies make emission observations difficult with current facilities except in the very local Universe (e.g., Chynoweth et al 2008;Lokhorst et al 2022) and rare cases with unusually high surface brightness. Consequently, emission observations of the IGM/ CGM often rely on deep, coadded observations averaging over hundreds to thousands of galaxies (e.g., Wisotzki et al 2016;Dutta et al 2023;Guo et al 2023aGuo et al , 2023b.…”
Section: Introductionmentioning
confidence: 99%
“…Recent IFS-enabled discoveries at lower redshifts of z < 1.5 revealed the potential for studies of ≈30-100 kpc-scale CGM nebulae observed in emission in nonresonant, rest-frame optical lines (e.g., [O II], Hβ, and [O III]) and resonant near-UV (NUV) lines (e.g., Mg II) around quasars (Johnson et al 2018;Helton et al 2021;Johnson et al 2022;Dutta et al 2023;Epinat et al 2024;Liu et al 2024), galaxy groups (Epinat et al 2018;Chen et al 2019;Leclercq et al 2022;Dutta et al 2023;Epinat et al 2024), and galaxies with evidence of recent bursts of star formation (Rupke et al 2019;Burchett et al 2021;Zabl et al 2021). The joint morphological and kinematic analysis of the nebulae combined with deep galaxy surveys enabled by IFSs provide direct insights into the origins of the gas, including interactions, accretion, and outflows.…”
Section: Introductionmentioning
confidence: 99%